2020
DOI: 10.1016/j.dib.2019.104874
|View full text |Cite
|
Sign up to set email alerts
|

Data on the role of miR-144 in regulating fetal hemoglobin production in retinal pigmented epithelial cells

Abstract: The data presented in this article are connected to our related article entitled “Inhibiting microRNA-144 potentiates Nrf2-dependent antioxidant signaling in retinal pigmented epithelial cells (RPE) and protects against oxidative stress-induced outer retinal degeneration” [1] where, we have shown that miR-144 induces oxidative stress in RPE cells by targeting Nrf2 expression. Previous studies from our laboratory have shown that like erythroid cells, RPE cells express α, β and γ-globin and produce hemoglobin lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Many studies have been conducted on retinal epithelial damage caused by oxidative stress and inflammation, and recent studies have shown that the redox-sensitive microRNA (miR)-144 plays an important role in the regulation of antioxidant signaling pathways in human and mouse RPE. Oxidative stress enhanced the expression of miR-144-3p and mir-144-5p, decreased expression of Nrf2 and downstream antioxidant target genes Nqo1 and Gclc , decreased glutathione levels, and increased RPE cell death ( Yam et al, 2019 ; Jadeja and Martin, 2020 ). In summary, oxidative stress and inflammation cause RPE cell damage, which in turn causes retinal dysfunction and even blindness.…”
Section: Retinal Pigment Epithelial Diseases and Pathogenesismentioning
confidence: 99%
“…Many studies have been conducted on retinal epithelial damage caused by oxidative stress and inflammation, and recent studies have shown that the redox-sensitive microRNA (miR)-144 plays an important role in the regulation of antioxidant signaling pathways in human and mouse RPE. Oxidative stress enhanced the expression of miR-144-3p and mir-144-5p, decreased expression of Nrf2 and downstream antioxidant target genes Nqo1 and Gclc , decreased glutathione levels, and increased RPE cell death ( Yam et al, 2019 ; Jadeja and Martin, 2020 ). In summary, oxidative stress and inflammation cause RPE cell damage, which in turn causes retinal dysfunction and even blindness.…”
Section: Retinal Pigment Epithelial Diseases and Pathogenesismentioning
confidence: 99%
“…Antioxidant levels in cells are reduced in degenerative retinopathy. Many studies on retinal epithelium damage caused by oxidative stress and in ammation have been conducted, and recent studieshave shown that redox-sensitive microRNA (miR) play a signi cant role in the regulation of antioxidant signaling pathways in human and rat RPEs [29]. RPE cell damage is caused by oxidative stress and in ammation, which leads to retinal dysfunction and even blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Redox-sensitive miRNAs play an important role in the regulation of antioxidant signaling pathways in the RPE. Recent studies have shown that OS enhances the expression of miR-144-3p and mir-144-5p, which block the expression of Nrf2 and controlled target genes for antioxidants Nqo1 and Gclc, reducing the content of GSH in human and mouse RPE and increasing cell death [ 354 , 355 ]. Nrf2 is a target gene of miR-93; the overexpression of Nrf2 alleviates the high glucose-induced apoptotic effect of ARPE-19 cells and can reverse the pro-apoptotic effect and inflammation of miR-93 [ 356 ].…”
Section: The Exogenous Regulation Of Redox Homeostasis Of Rpe Cellsmentioning
confidence: 99%